IMPROVING STUDENTS’ LEARNING OUTCOMES BY USING MIND MAPPING LEARNING MODEL AT GRADE III SD NEGERI 030441 PAMAH - Pondang Elisabet Siallaga; Patri Janson Silaban; Asnita Hasibuan (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
The type of this research was action research (classroom research). The subjects in this study were 30 students at grade III SD Negeri 030441 Pamah, consisting of 15 boys and 15 girls. The object of this research is Mind Mapping learning model as an effort to improve students’ learning outcomes. The results of this study indicated an increase in the students’ learning outcomes through Mind Mapping model on the theme of “Menyayangi Tumbuhan dan Hewan” at grade III SD Negeri 030441 Pamah. It was found that in the pre-test, 8 students (27%) completed the learning objectives while 22 students (73%) did not complete the learning objective with the average score of 59.93. Meanwhile, the average score in the posttest of cycle I increased to 66.4 in which 13 students (43%) completed the learning objective while 17 students (57%) did not complete the learning objective. Moreover, the result of the post test in cycle II found that 25 students (83%) completed the learning objective while 5 students (17%) did not complete the learning objective with an average score of 80.06. Furthermore, the results of observations to teachers’ activities in Cycle I obtained a value of 78% (good), and in Cycle II it increased to 92% (very good). Similarly, the results of observations to students’ activities also increased from 78% (good) in Cycle I to 90% (very good) in Cycle II.